2018
DOI: 10.1093/ejcts/ezx497
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of pulmonary valve annular enlargement with valve repair in tetralogy of Fallot

Abstract: PV annular enlargement with valve repair has reasonable long-term results and yields a lower long-term incidence of significant PR compared with the simple transannular patch enlargement technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 19 publications
2
19
0
1
Order By: Relevance
“…In the literature, pulmonary valve repair methods have been reported along with pulmonary valve annulus enlargement. Kim et al 7 reported the long‐term outcomes of pulmonary annulus enlargement and valve repair to 43 patients. In the early period, the mean PI rates were 0.93 ± 0.40 and the mean RVOT gradients were 13.0 ± 10.9 mm Hg.…”
Section: Commentmentioning
confidence: 99%
See 3 more Smart Citations
“…In the literature, pulmonary valve repair methods have been reported along with pulmonary valve annulus enlargement. Kim et al 7 reported the long‐term outcomes of pulmonary annulus enlargement and valve repair to 43 patients. In the early period, the mean PI rates were 0.93 ± 0.40 and the mean RVOT gradients were 13.0 ± 10.9 mm Hg.…”
Section: Commentmentioning
confidence: 99%
“…Various methods have been described for prevention of PI during RVOT reconstruction with transannular patch 1‐8 . These techniques include monocusp valve placement and anterior leaflet augmentation with polytetrafluoroethylene membranes.…”
Section: Commentmentioning
confidence: 99%
See 2 more Smart Citations
“…Although this series is small and its follow-up is limited, these results are impressive and quite thought-provoking. In comparison with other reported techniques for a functional valve-sparing repair, which mainly rely on cusp augmentation, 5,6 it appears that the potential advantage of the Padua group's approach 3 is the aggressive use of native tissue. The use of leaflet delamination extending into the subannular plane when necessary followed by leaflet resuspension avoids the need for any major nonanatomic (biologic or not) cusp reconstruction.…”
mentioning
confidence: 99%